Effects of geological formations and topography on the evolution and diversity of soils (Nexo Revista Científica, 2020)
Different soils with various properties and sometimes with different types of limitations can be formed which is necessary to investigate the conditions of soil formation and evolution for their optimal use. In this study, we studied the relationship between soil, topography in terms of slope and elevation, and parent material with the land morphology and physical and chemical properties of soil, how the soil formed and evolved. From 19 control soil profiles, 57 soil samples were obtained from three layers and some soil characteristics including Acidity, Salinity, Gypsum, Lime, Texture and Organic matter were measured. Using NEWHALL software, the soil temperature and moisture regime was determined. To study the conditions of topography, the digital elevation map and slope was prepared, the characteristics of geological formations were determined and based on the Gower index and Jacquard index, the relationship between soil evolution factors with topography and parent materials were studied. The diversity of soils classification was studied using richness, uniformity of Shannon and Simpson indices. Based on the results obtained from Gower and jacquard similarity indices, the effect of topography and parent materials on soil diversity was proved. Soil diversity indices showed an increasing trend from the soil order level to the soil family. The increase in the Richness index was higher at the soil family level, so that the highest soil diversity observed at the soil family level. Also, soil diversity is mainly affected by intrinsic factors and to some extent by environmental factors. Soil profile development is mostly influenced by slope, parent materials and in some areas by groundwater level.